2005
DOI: 10.3201/eid1105.041251
|View full text |Cite
|
Sign up to set email alerts
|

Venezuelan Equine Encephalitis Virus Infection of Spiny Rats

Abstract: Enzootic strains of Venezuelan equine encephalitis virus (VEEV) circulate in forested habitats of Mexico, Central, and South America, and spiny rats (Proechimys spp.) are believed to be the principal reservoir hosts in several foci. To better understand the host-pathogen interactions and resistance to disease characteristic of many reservoir hosts, we performed experimental infections of F1 progeny from Proechimys chrysaeolus collected at a Colombian enzootic VEEV focus using sympatric and allopatric virus str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…Additional selective forces on the RNA genome sequence related to genomic or subgenomic RNA replication, secondary structure, and͞or packaging could complicate the selection of such mutations in nature and should be studied further. A population size of 10 4 is exceeded in infected mosquitoes, which generally develop titers of Ϸ10 6 infectious units, including Յ10 4 in the saliva (40,41) and in reservoir hosts such as spiny rats (42,43) and cotton rats (42,44), which develop peak viremia titers exceeding 10 4 infectious units͞ml. This finding suggests that ecological factors including transport of nascent epidemic strains to locations conducive to equine amplification, as well as epidemiologic and ecologic factors including equine herd immunity and mosquito densities, constrain the frequency of VEE epidemics rather than the generation of amplification-competent mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Additional selective forces on the RNA genome sequence related to genomic or subgenomic RNA replication, secondary structure, and͞or packaging could complicate the selection of such mutations in nature and should be studied further. A population size of 10 4 is exceeded in infected mosquitoes, which generally develop titers of Ϸ10 6 infectious units, including Յ10 4 in the saliva (40,41) and in reservoir hosts such as spiny rats (42,43) and cotton rats (42,44), which develop peak viremia titers exceeding 10 4 infectious units͞ml. This finding suggests that ecological factors including transport of nascent epidemic strains to locations conducive to equine amplification, as well as epidemiologic and ecologic factors including equine herd immunity and mosquito densities, constrain the frequency of VEE epidemics rather than the generation of amplification-competent mutants.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 5 of the most commonly captured rodent species in coastal Chiapas, Mexico, were evaluated for their ability to participate in the natural transmission cycle of enzootic VEEV-IE. S. hispidus and O. capito rodents have previously been implicated in amplifi cation of other VEE subtypes, ID, IE, and II (7)(8)(9) Figure 3. Relatedness of 7 wild rodent genera that have been experimentally evaluated for suitability as amplifying hosts in enzootic transmission cycles of Venezuelan equine encephalitis virus.…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…These viruses are thought to circulate continuously among mosquitoes and their principal vertebrate amplifying hosts, whereas horses and humans are considered spillover, dead-end hosts not required for maintenance of the natural cycle. Several studies have shown that terrestrial mammals of 5 genera (Didelphis, Oryzomys, Proechimys, Sigmodon, and Zygodontomys) are susceptible to VEEV-IE infection; they develop viremia suffi cient to infect mosquito vectors, yet they usually survive infection (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Cx. vomerifer was found to be infected with certain arboviruses such as Caraparu (Brazil, Panama), Guama (Colombia, Peru), Itaqui (Brazil, Venezuela), Moju (Venezuela), Murutucu (Belém), Ossa (Panama), Ananindeua, Vinces, Madrid and other types of Bunyaviridae (Shope et al 1988, Walter Reed Report 1998, Carrara et al 2005. Cx.…”
Section: Discussionmentioning
confidence: 99%